Creation and assessment of a clinical predictive model for candidaemia in patients with candiduria. Issue 7 (22nd May 2019) - Wang, Katie; Hsueh, Kevin; Kronen, Ryan; Lin, Charlotte; Salazar, Ana S.; Powderly, William G.; Spec, Andrej
Summary: Candidaemia is the most common clinical presentation of invasive candidiasis and is a major cause of morbidity and mortality. Candiduria is a predictor for candidaemia; however, patient characteristics that are associated with concurrent candidaemia in the setting of candiduria are unclear. Identifying these characteristics could aid in the early detection of systemic disease. We performed a retrospective cohort analysis of hospitalised patients with candiduria at our institution over a 13‐year period. Our evaluation of patient characteristics included demographics, comorbidities, medications, procedures, devices, vital signs and laboratory values. We developed a multivariable logistic model to identify factors associated with candidaemia in patients with candiduria. We identified 4240 patients with candiduria, 263 (6.2%) of whom had candidaemia. Predictors for increased risk of candidaemia with candiduria included hospitalisations > 12 days, central venous catheter, parenteral nutrition, haematological and gynaecological malignancy, and receipt of β‐lactam/β‐lactamase inhibitors. Vital signs and laboratory values associated with candidaemia included elevated heart rate, temperature and creatinine, along with neutropenia and neutrophilia. Factors that demonstrated a decreased risk of candidaemia included diabetes mellitus, gastrostomy and urinary catheter with antibiotic use. The c‐statistic was 0.741 (95% CI, 0.710‐0.772). We identified a set of clinical characteristics that can predict the presence of candidaemia with candiduria.